Оценка тепловых эффектов в процессе полимеризации α-метилстирола - Ляпков А. А. Алексей Алексеевич; Бондалетов В. Г. Владимир Григорьевич; Ионова Е. И. Елена Ивановна; Пуленските И. Р. (2007, 2007)
Заглавие с экрана